Odpowiedź:
W(x) = x⁴ - 2x³ + px² + 4x + q ; x₁ = - 1 , x₂ = 3
1.
Podstawiamy do równia za x wartość ( - 1) i wtedy wartość wyrażenia powinna wynosić 0
0 = (- 1)⁴ - 2 * (- 1)³ + p * (- 1)² + 4 * (- 1) + qg
0 = 1 - 2 * (- 1) + p * 1 - 4 + q
0 = 1 + 2 + p - 4 + q
0 = p + q - 1
p + q = 1
2.
Podstawiamy do równia za x wartość 3 i wtedy wartość wyrażenia powinna wynosić 0
0 = 3⁴ - 2 * 3³ + p * 3² + 4 * 3 + q
0 = 81 - 2 * 27 + 9p + 12 + q
0 = 81 - 54 + 9p + 12 + q
0 = 15 + 9p + q
9p + q = - 15
3. Układ równań
9p + q = - 15
p + q = 1
Odejmujemy równania
9p - p + q - q = - 15 - 1
8p = - 16
p = - 16/8 = - 2
p + q = 1
- 2 + q = 1
q = 1 + 2 = 3
Odp: p = - 2 , q = 3